Effect of Soluplus on the supersaturation and absorption of tacrolimus formulated as inclusion complex with dimethyl-β-cyclodextrin. (21st October 2019) - Tao, Chun; Huo, Taotao; Zhang, Qian; Song, Hongtao
Abstract: The application of tacrolimus (FK506) is hampered by its poor solubility and dissolution, which can be promoted by the use of inclusion complex. However, in supersaturated environment, crystallization of the drug inclusion complex may occur, leading to reduced absorption in vivo . In this study, Soluplus, an amphiphilic copolymer of polyvinyl caprolactam, polyvinyl acetate and polyethylene glycol, was used to improve the supersaturated stability and absorption of FK506. Using dimethyl-β-cyclodextrin (DM-β-CD), the inclusion complex (FK506-CD) was prepared, which showed favorable dissolution profiles. But in supersaturated condition, the drug concentration was rapidly decreased, with 10.64 ± 0.69 μg/ml of FK506 at 12 h. Ternary complex (FK506-SCD) containing Soluplus contributed steadier drug concentration. The FK506-SCD with 1.2% Soluplus best promoted the supersaturated stability of the inclusion complex, with 62.90 ± 3.34 μg/ml of FK506 at 12 h. Soluplus also reduced the crystallization and degradation of FK506 in the stress test. In the single-pass intestinal perfusion test, the absorption of FK506 in the ileum and colon was significantly increased. Pharmacokinetic results showed that the bioavailability of FK506-SCD was 2.34-fold that of FK506-CD. Our data suggested that Soluplus had an excellent capability in improving the supersaturated stability and in vivo absorption of FK506 inclusion complex.